Catalytic Activity of Titanium and Ruthenium Oxide Nanosheets in the Oxygen Reduction Reaction. (2019) - Saida, Takahiro; Mashiyama, Miyu; Maruyama, Takahiro
Abstract: Monolayer molecular electrodes composed of titanium oxide nanosheets (TiO2 ns) or ruthenium oxide nanosheets (RuO2 ns) were prepared and their activities in the oxygen reduction reaction (ORR) were evaluated to investigate the ORR active sites in oxide catalysts. In TiO2 ns, the influence of physical distortion sites in the crystal structure formed by introducing oxygen vacancies was determined. The ORR activity of TiO2 ns was improved by introducing physical distortion sites. In RuO2 ns, the effects of both the type of crystal structure and electrochemical distortion sites arising from redox reactions on ORR performance were studied. The type of crystal structure had almost no effect on ORR activity. In contrast, electrochemical distortion sites were expected to behave as the ORR active sites because the on-set potential of the ORR was similar to the redox peak position for the RuO2 ns. Thus, the distortion sites in oxide crystal structures may behave as the active sites in the ORR independent of the metal species.